Autumn Peltier, water warrior - Lindstrom, Carole, 1964- (Roaring Brook Press, 2023)
Indigenous women have always worked tirelessly to protect our water -- keeping it pure and clean for the generations to come. Yet there was a time when their voices and teachings were nearly drowned out, leaving entire communities and environments in danger and without clean water. But then came Grandma Josephine and her great-niece, Autumn. Speak for the water. Sing for the water. Dance for the water. With moving lyricism and arresting illustrations, Carole Lindstrom and Bridget George celebrate Josephine Mandamin and Autumn Peltier, two groundbreaking water warriors who have created a tidal wave of change.